The effect of vitamin D supplementation on selected inflammatory biomarkers in obese and overweight subjects: a systematic review with meta-analysis - Jamka, Małgorzata; Woźniewicz, Małgorzata; Walkowiak, Jarosław; Bogdański, Paweł; Jeszka, Jan; Stelmach-Mardas, Marta (European journal of nutrition, 2016)
Purpose The objective of this systematic review was to assess the effect of vitamin D supplementation on selected inflammatory biomarkers in obese and overweight subjects. Methods The search process was based on the selection of publications (DB-RCT and RCT) listed in the following databases: PubMed, Web of Knowledge, Scopus, the Cochrane Library and Embase. To assess the study quality, a nine-point scoring system according to the Newcastle–Ottawa scale was used, and a high-quality study was defined by a threshold of ≥7 points. Thirteen randomized controlled trials were included. The analysed population consisted of 1955 overweight and obese subjects. The mean age ranged from 13.6 to 71.7 years. Changes in the concentration of 25-hydroxycholecalciferol (25(OH)D), C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6) were assessed. To combine individual study results, a meta-analysis was performed. Results The baseline levels of 25(OH)D suggested vitamin D deficiency or insufficiency in the analysed population. The vitamin D supplementation did not influence on CRP (std. mean differences −0.11; 95 % CI −0.27–0.04; p = 0.15), TNF-α (std. mean differences −0.13; 95 % CI −0.38–0.12; p = 0.31) and IL-6 concentrations (std. mean differences 0.1; 95 % CI −0.43–0.63; p = 0.71). Conclusions This meta-analysis suggests that supplementation with vitamin D does not have a significant influence on changes in the concentration of selected inflammatory biomarkers in the obese and overweight subjects.